HOUSING AND COMMUNAL SERVICES ALGORITHMS FOR THE FORMATION OF A RATIONAL COMPOSITION OF THE PROVISION AND CONSUMPTION OF SERVICES. - Adilova Yulduz Shavkatovna (World Scientific Research Journal, 2025)
Annotation: housing and communal services are an important component of the country’s national economy. It occupies a worthy place in the socio-economic development of the country, in particular, in the satisfaction of its needs, in improving the standard and quality of life of the population, in the formation of the state budget. In parallel, housing and communal services are a multidisciplinary field and activities in different directions. This sector is inextricably linked with other sectors of the national economy, which interact with each other’s development.